Extracorporeal cardiopulmonary resuscitation-based approach to refractory out-of-hospital cardiac arrest: A focus on organ donation, a secondary analysis of a Prague OHCA randomized study - Smalcova, J; Havranek, S; Pokorna, E; Franek, O; Huptych, M; Kavalkova, P; Pudil, J; Rob, D; Dusik, M; Belohlavek, J (Resuscitation, 2023)
BACKGROUND: Refractory out-of-hospital cardiac arrest (OHCA) has a poor outcome. In patients, who cannot be rescued despite using advanced techniques like extracorporeal cardiopulmonary resuscitation (ECPR), organ donation may be considered. This study aims to evaluate, in refractory OHCA, how ECPR versus a standard-based approach allows organ donorship. METHODS: The Prague OHCA trial randomized adults with a witnessed refractory OHCA of presumed cardiac origin to either an ECPR-based or standard approach. Patients who died of brain death or those who died of primary circulatory reasons and were not candidates for cardiac transplantation or durable ventricle assist device were evaluated as potential organ donors by a transplant center. In this post-hoc analysis, the effect on organ donation rates and one-year organ survival in recipients was examined. RESULTS: Out of 256 enrolled patients, 75 (29%) died prehospitally or within 1 hour after admission and 107 (42%) during the hospital stay. From a total of 24 considered donors, 21 and 3 (p = 0.01) were recruited from the ECPR vs standard approach arm, respectively. Fifteen brain-dead and none cardiac-dead subjects were ultimately accepted, 13 from the ECPR and two from the standard strategy group. A total of 36 organs were harvested. The organs were successfully transplanted into 34 recipients. All transplanted organs were fully functional, and none of the recipients died due to graft failure within the one-year period post-transplant. CONCLUSION: The ECPR-based approach in the refractory OHCA trial is associated with increased organ donorship and an excellent outcome of transplanted organs. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01511666. Registered January 19, 2012.
Keywords: Extracorporeal Membrane Oxygenation; Cardiopulmonary Resuscitation; Tissue and Organ Procurement; zástava srdce mimo nemocnici; transplantace orgánů; Adult; dospělí; retrospektivní studie; Out-of-Hospital Cardiac Arrest; Humans; Organ Transplantation; lidé; kardiopulmonální resuscitace; Retrospective Studies; mimotělní membránová oxygenace; získávání tkání a orgánů